STUDI KINERJA ORGANISASI DI KANTOR PERTANAHAN KABUPATEN SUKOHARJO - Retno Setyaningsih; Hesti Lestari; Maesaroh Maesaroh (Journal of Public Policy and Management Review, 2013)
Land Office of Sukoharjo district is a vertical institution of the National Land Agency (BPN), which was and is directly responsible to the Head of BPN Regional Office of Central Java Province that serving community activities in soil sertification in Sukoharjo District. Land Office of Sukoharjo district is a land office by the number of applicants the second largest land title services in Central Java Province.This study aims to identify and analyze the support factors and hinder organizational performance in Land Office of Sukoharjo District, so as to know what needs to be improved and sustained performance.The supporting factors and inhibiting factors are identified and analyzed from the organizational structure, policies, management, human resource management, technology, environment, organizational culture and leadership.In this study, researchers used a purposive technique. Data collection methods used were in-depth interviews and documentation techniques. This study shows that the supporting factors of the organization's performance at the Land Office of Sukoharjo District, among other things, policies related to the vision and mission management, human resource management through the aspects of compensation, incentives, and education and training, appropriate technology, environmental organizations, cultural organizations, and leadership. Limiting factor is the organizational structure in the aspect of unit size that shows the number of employees that are not balanced by a large request and sentraisasi decision making which is often prolonged vacancy, then from their own community who do not understand the procedures and delay in completing service file so that it becomes hampered the process.